2015
DOI: 10.1016/j.rser.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Is the long-run relationship between economic growth, electricity consumption, carbon dioxide emissions and financial development in Gulf Cooperation Council Countries robust?

Abstract: The relationship between carbon dioxide emissions, economic growth, electricity consumption and financial development in the Gulf Cooperation Council (GCC) countries is investigated in this study using panel data for the period of 1980-2012. A number of econometric techniques: dynamic ordinary least squares (DOLS), fully modified ordinary least squares (FMOLS) and the dynamic fixed effect model (DFE) are applied in order to estimate the long-run relationship between the variables. The long-run relationship is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
172
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(195 citation statements)
references
References 56 publications
22
172
0
1
Order By: Relevance
“…On the nexus between CO 2 emissions, economic growth, electricity consumption and financial development in six Gulf Cooperation Council (GCC) countries, Salahuddin, Gow, and Ozturk (2015) employed panel data for the period of 1980-2012 and various methods (dynamic ordinary least squares (DOLS), FMOLS and the dynamic fixed effect (DFE) models) to examine the long-run relationship between the variables. Results showed that electricity consumption and economic growth have a positive long run relationship with CO 2 emissions while financial development had a negative and significant relationship.…”
Section: Non-regime Switching Panel Methodsmentioning
confidence: 99%
“…On the nexus between CO 2 emissions, economic growth, electricity consumption and financial development in six Gulf Cooperation Council (GCC) countries, Salahuddin, Gow, and Ozturk (2015) employed panel data for the period of 1980-2012 and various methods (dynamic ordinary least squares (DOLS), FMOLS and the dynamic fixed effect (DFE) models) to examine the long-run relationship between the variables. Results showed that electricity consumption and economic growth have a positive long run relationship with CO 2 emissions while financial development had a negative and significant relationship.…”
Section: Non-regime Switching Panel Methodsmentioning
confidence: 99%
“…The subsequent economic stimulus, environmental preservation, and improvement to social system are pillars of sustainability. Several studies have assessed the renewable energy targets for specific regions separately, e.g., the USA [3], China [4], India [5], Malaysia [6,7], Taiwan [8], Germany [9], Turkey [10,11], The Netherlands [12] and Spain [13,14], or multi-countries, e.g., the Gulf Cooperation Council (GCC) countries [15], South Asian Association for Regional Cooperation (SSARC) countries [16], BRICS countries [17], and European Union (EU) [18,19]. Because country targets might have strong spillover effects into other regions, it is vital to study renewable energy targets on global scale.…”
Section: Introductionmentioning
confidence: 99%
“…causality test and showed there was a bidirectional causal link between economic growth and CO 2 emissions [6]. There are also a large number of literature apply the causality test to study the relationship between GDP and CO 2 emissions in domestic.…”
Section: Advances In Economics Business and Management Research (Aebmentioning
confidence: 99%